The effectiveness of the Surgical Safety Checklist as a means of communication in the operating room - Michael, Rene; Della, Phillip; Zhou, Huaqiong (Cambridge Publishing, 2013)
This paper reports an integrative research review (IRR) on the effectiveness of implementing the Surgical Safety Checklist (SSC) as a means of communication in the operating room. A total of11 studies conducted in 2012 were included in this review. Two main themes with subthemes emerged from the analysis. The first theme is Administration of the SSC with two subthemes: Compliance rate with the SSC and Completion of the SSC. The second theme was titled Outcomes of implementing the SSC with a subsequent four subthemes arising: Verification of information, Mortality and complications, Adverse events, and Incidents. This IRR revealed that implementation of the SSC had consistent positive outcomes in the reduction of preventable harm to patients undergoing surgeries. It is, however, recommended that further training in utilising the SSC and strategies is needed to ensure full compliance and completion rate with the SSC.